Genomic analysis of Campylobacter risk in retail chicken isolated from Beijing in 2024 - Jianyun Zhao; Ying Liu; Menghan Li; Ruicheng Zheng; Xin Gan; Lanqi Li; Séamus Fanning; Dejun Liu; Yang Wang; Juan Wang; Li Bai (International Journal of Food Microbiology, 2026)

Brittle–ductile transition in dehydrated and rehydrated gypsum: Effects of reaction-induced bi-phase evolution - Yang Zheng; Kang Duan; Di Wang; Huiru Lei; Qiangyong Zhang; Dejun Liu; Ziyi Geng (International Journal of Rock Mechanics and Mining Sciences, 2026)

Influence of structural parameters on characteristics of flow field in vessel-shaped aquaculture cages - Hongzhou Chen; Xucheng Jiang; Dejun Feng; Xu Yang; Lili Mei (Ocean Engineering, 2026)

Resistance-oriented dose-response modeling for quantitative risk assessment of nontyphoidal Salmonella in retail pork - Huanyan Si; Zhiyu Zou; Dejun Liu; Jianyun Zhao; Pengfei Liu; Yang Wang; Jianzhong Shen; Lu Wang; Li Bai (Food Control, 2026)

Seismic performance of full-scale modular steel frame: Components and joints - Chao Yang; Lifei Feng; Hao Zhang; Dejun Zhang; Jinping Ou (Engineering Structures, 2026)

Pull-out performance and damage monitoring of cast SHS grouting sleeve connection for modular steel building - Chao Yang; Liangsheng Qiu; Dejun Zhang; Siqi Ding; Lu Zhou; Jinping Ou; Yi-Qing Ni (Engineering Structures, 2026)

Bifidobacterium longum engineered with artificial enzymes alleviates high-altitude colitis via inhibition of GPD2-dependent ferroptosis - WenQiang Yuan; Fang Yan; LiuChan Yang; YunHan Yang; Chen Chen; ShiMin Wu; DeJun Cui (Protoplasma, 2026)

Co-exposure to lead and copper induces ferroptosis-related neurotoxicity in zebrafish larvae via oxidative stress and mitochondrial dysfunction - Samra; Rongjian Liu; Xuan Ma; Jiamin Shi; Dongqiong Wei; Lei Yang; Qian Li; Cong Yuan; Yongmei Qi; Yingmei Zhang; Dejun Huang (Journal of Hazardous Materials, 2026)

Experimental investigation into the dynamic and mooring response of a novel submersible cage to waves at various depths - Wenjian Wang; Dejun Feng; Can Cui; Meihan Chen; Tianrui Ji; Xu Yang; Hongzhou Chen; Hua Zhang; Jiajun Hu; Lianhui Wu; Fukun Gui; Xiaoyu Qu (Ocean Engineering, 2026)

Electron Transfer Drives Preferentially Assimilatory Sulfate Reduction in Petroleum‐Contaminated Soil - Jialu Sun; Yuewei Yang; Xin Yu; Xiaolin Zhang; Pinpin Yang; Bingyang Liu; Yali Chen; Dejun Wang; Xinhong Peng; Xiaojing Li (Environmental Microbiology, 2026)
Sulfur is a vital macroelement for soil fertility and crop growth, and its bioavailability is converted with electron flux. To determine the effect of biological electron transfer on the sulfur cycle in soil, a microbial electrochemical system (MES) was established to amplify the efficiency of extracellular electron transfer. Results showed that biocurrent obviously promoted the reduction of water‐soluble SO 4 2‐ to S 2− , and afterward reoxidised to fulvic acid sulfur (FAS, 32% increment) instead of humic acid sulfur (HAS, 77% decrement). The δ 34 FAS values (12‰ to 24‰) were consistent with the typical isotopic signatures of dissimilatory sulfate reduction, while the δ 34 HAS values (−40‰ to −60‰) matched the assimilatory sulfate reduction. Meanwhile, the assimilatory SO 4 2‐ reduction to cysteine improved with a 30%–33% increase for the NAD + /NADH and secretion of cytochrome c to support robust redox. Essentially, the precursor‐product pairs of desulfonation were enhanced by 26%–93%. Compared to a 6% contribution of HAS, the formation of cysteine accounted for 55% of the electron transport flux. According to screening 32 sulfur‐transforming genes, 609 genera were identified, especially 31%–84% proliferation for Desulfatitalea . This study reveals ways of organic sulfur conversion mediated by electron transfer, which can assist the biological amendment of sulfur bioavailability in soil.

Mechanistic insights into electric-field-induced ice suppression and ion migration in ice-channel-confined NaClO4 electrolyte - Zhenyu Zhang; Dejun Xiong; Zizhen Yan; Yang Guo; Heng Zhang; Shiling Yuan (Chemical Engineering Journal, 2026)

Precise mapping of high-temperature adult-plant stripe rust resistance gene Yr52 in wheat - Mingjie Xiang; Yibo Zhang; Shuaiwei Cao; Jiangna Han; Haohao Yan; Chenfang Wu; Jiale Li; Xunying Yuan; Xiangrui Cheng; Shuqing Yang; Zhuang Li; Xiaoting Wang; et al. (Theoretical and Applied Genetics, 2026)

Tree Species Diversity Suppresses Soil Carbon Priming Effects in a Subtropical Forest - Pengpeng Duan; Xinyi Yang; Andrew T. Nottingham; Chaoqun Wang; Luiz A. Domeignoz‐Horta; Wolfgang Wanek; Xinli Chen; Yuqi Zhou; Hongzhao Yuan; Hu Du; Kelin Wang; Dejun Li (Ecology Letters, 2026)
Nature‐based climate solutions rely on the assumption that restoring plant diversity enhances soil organic carbon (SOC) sequestration. However, the persistence of SOC is threatened by the positive priming effects, where fresh plant carbon inputs accelerate the decomposition of native SOC. It remains unclear how increasing plant diversity impacts the soil priming effects. Here, using a natural tree species diversity gradient in a subtropical forest, we show that higher tree diversity was strongly associated with suppressed soil priming effects, attributable to reduced mineral protection of SOC and alleviated microbial energy limitation. Microbial community consequently shifts toward fast‐growing specialists that outcompete decomposers of chemically complex carbon. Our study reveals that tree species diversity is a key regulator of SOC persistence and demonstrates that the biodiversity‐driven priming suppression should be explicitly incorporated into nature‐based climate solutions and Earth system models to reduce critical uncertainties in carbon cycle projections.

Biomass models, allometric relationships, and carbon sink of Sargassum henslowianum in Nan'ao Island - Jing Chen; Jinhuai Ni; Hong Du; Kai Zong; Sunzhaocong Lan; Jianpeng Lu; Dejun Feng; Xu Yang; Guangyang Zhang; Lili Mei; Yuanmin Sun; Xunmeng Li (Regional Studies in Marine Science, 2026)

Rapid retreat of the East Asian summer monsoon at the end of the Holocene humid period accelerated the transition from broadleaf to pine forest landscapes in northern China - Linjing Liu; Xin Mao; Lei Song; Xingqi Liu; Dejun Wan; Gaolei Jiang; Jingsong Yang; Hongmei Zhao; Chengmin Wang; Hua Zhao; Rong Ma (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Enhancing Phytoremediation of Multi-Metal Contaminated Soil by Tagetes patula L. using Amycolatopsis tucumanensis KC 316 - Xiaoming Wang; Yajie Wu; Dejun Kong; Haotian Dong; Changyou Zhao; Murad Muhammad; Jing Zhang; Yuanchun Yang; Rui Liu; Shuai Wang; Aoli Zhang; Chunmei Lu; et al. (Journal of Environmental Sciences, 2026)

Stochastic and deterministic processes shape microbiota and flavors of strong-flavor Daqu made from different wheat varieties during fermentation - Kangjie Yu; Rong Yang; Huiling Huang; Shuanghui Wang; Chaojiu He; Liya Huang; Yi Ma; Dejun Han (Food Research International, 2026)

Ferrihydrite accelerates carbon turnover by regulating interspecific electron transfer in petroleum-contaminated soil - Xin Yu; Yuewei Yang; Jialu Sun; Pengju Zhong; Xiaolin Zhang; Jing He; Zhiwen Lin; Dejun Wang; Wenqing He; Xiaojing Li (Chemical Engineering Journal, 2026)

A ROS scavenging multifunctional hydrogel crosslinked with EGCG promotes the healing of pressure injuries via Nrf2 pathway - Yingying Pan; Jiaying Lou; Yuqi Wang; Rongfang Dai; Miwen Zou; Danni Ma; Shengzhang Chen; Jinghao Zhou; Binyan Chen; Xiaoqiong Jiang; Pan Huang; Huaqiong Li; et al. (Chemical Engineering Journal, 2026)

Permafrost degradation: A critical driver of aboveground carbon sink loss in China's boreal forests - Hong Yang; Jie Tang; Xiaoqing Chang; Jiaqi Wang; Weishu Gong; Dejun Wang; Yanqiu Xing (CATENA, 2026)

Assessing the behavior of Larimichthys crocea during the ascent process of the offshore submersible cage - Jinhuai Ni; Sunzhaocong Lan; Yang Gao; Xiaolong Yin; Kai Zong; Jianpeng Lu; Xu Yang; Fukun Gui; Xunmeng Li; Dejun Feng (Aquaculture, 2026)

Corrigendum to “Integration of transcriptomics and metabolomics reveals the effects of sea currents on overwintering of large yellow croaker Larimichthys crocea in cage culture” [Aquaculture, volume 578, 15 January 2024, 740054]. - Huirong Lv; Xiaoyu Qu; Zhangjie Chu; Weiye Li; Xiaolong Yin; Dejun Feng; Jungyeol Park; Junwook Hur; Yang Gao (Aquaculture, 2026)

Artificial bio-cables of carbon fiber filaments bridge microbial electron flow and hydrocarbon degradation in soil - Side Yang; Xiaolin Zhang; Xiaodong Zhao; Kai Wang; Dejun Wang; Wenqing He; Xiaojing Li; Yongtao Li (Journal of Hazardous Materials, 2026)

Study on the degradation performance and toxicity reduction mechanism of electroplating wash wastewater by a hydrolysis–acidification–MPR synergistic system - Weiqing Jiang; Jinhao Pu; Fan Wang; Jiulin Yan; Qing Yang; Siwen Yang; Dejun Bian (Journal of Environmental Management, 2026)

Ecological responses of the largest lake-wetland system (North China Plain) to hydrological regulation and cultural eutrophication over the past 70 years - Longjuan Cheng; John P. Smol; Qi Lin; Chaoran Wei; Shuyi Yang; Dejun Wan; Qingfeng Jiang; Dongliang Ning; Bin Xue (Anthropocene, 2026)

Co-occurrence of mcr-1.1, mcr-3.40, and tmexCD1-toprJ1 on a hybrid IncFIB/IncHI1B plasmid in Klebsiella pneumoniae from pork in Hainan, China - Hanzhang Cai; Lu Liu; Yao Wang; Yingbo Shen; Congming Wu; Dejun Liu; Yang Wang; Xueliang Zhao; Weishuai Zhai (International Journal of Food Microbiology, 2026)

Multi-Target Anticoagulant Regulation by Peptides from Medicinal Leeches: A Unique Natural Strategy against Thrombosis - Feng Shi; Qingmei Hu; Yiquan Lin; Sijia Fan; Xueting Cao; Dezhi Yang; Yuanhai Chen; Dejun Kong; Kaiqing Liu; Zichao Liu (Pharmaceutical Research, 2026)

RC-UMT: Multimodal fish feeding intensity classification network with enhanced feature extraction capability in aquaculture - Shantan Li; Xinting Yang; Zhitao Huang; Tingting Fu; Pingchuan Ma; Dejun Feng; Chao Zhou (Aquacultural Engineering, 2026)

Enhancing SUHI monitoring in mountainous cities: A comparative study of Chongqing and Chengdu, China - Dejun Zhang; Shiqi Yang; Hao Zhu; Qinyu Ye; Zeneng He; Wan Zhou; Yuyu Zhou (Urban Climate, 2025)

Tree species diversity enhances dark microbial CO2 fixation rates in soil of a subtropical forest - Xintong Xu; Pengpeng Duan; Xinyi Yang; Dejun Li (Soil Biology and Biochemistry, 2025)

Interventional effects of Tsantan Sumtang in ischemic heart disease: an integrated network pharmacology and metabolomics approach - Panpan Wang; Dejun Zhang; Yongjing Yang; Dehua Gao; Yi Zhou (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Transcriptome analysis reveals differences in postharvest fruit firmness changes between two Kiwiberry varieties - Zhao Liu; Jianyu Song; Yuying Li; Yanhong Cui; Zeyang Zheng; Kexin Zhu; Taiming Liang; Zhenpan Liu; Yang Sun; Dejun Liang (Horticulture, Environment, and Biotechnology, 2025)

Ionic strength modulates size-controlled ecotoxicity of citrate-coated silver nanoparticles to Daphnia magna in complex environmental matrices - Ping Luo; Zhenghao Xu; Jiageng Zhang; Xin Wang; Xiujun Gu; Lizhang Wang; Dejun Yang; Jiachao Jiang (Environmental Geochemistry and Health, 2025)

Effect of urea concentration on the combined pollution of Cd and Ni in microbiologically induced calcite precipitation (MICP) treatment - Dejun Yang; Shengnan Bei; Yong Yang (Biodegradation, 2025)

Soil microbial phosphorus limitation constrains carbon use efficiency in subtropical forests - Pengpeng Duan; Chaoqun Wang; Wolfgang Wanek; Xinyi Yang; Peilei Hu; Kelin Wang; Dejun Li (Soil Biology and Biochemistry, 2025)

Deep learning-based species identification of gymnosperm xylem: The practice in digital forestry - Chang Zheng; Tuo He; Lichao Jiao; Yang Lu; Shoujia Liu; Tianxiao Li; Yuanyuan Miao; Dejun Feng; Jian Lin; Xian Feng; Zhonghua Huang; Min Yu; et al. (Computers and Electronics in Agriculture, 2025)

Afforestation-driven microbial nitrogen limitation promotes soil nitrous oxide production by ammonia oxidizers - Yuliang Pan; Jianyu Dang; Peng Li; Xinyi Yang; Kongcao Xiao; Kelin Wang; Pengpeng Duan; Dejun Li (Plant and Soil, 2025)

Morphological feature assessment of Larimichthys crocea for quality grading: a computer vision approach - Dejun Feng; Hang Liu; Lianhui Wu; Xiaoguo Ying; Xiaoyu Qu; Yang Gao; Fukun Gui; Chao Zhou (Aquaculture International, 2025)

Sustainable production of zinc ammonium chloride from hazardous oil sludge through integrated solvent-assisted metal leaching and byproduct recovery - Zheng Minglin; Lan Xin; Yang dandan; Kang Hua; Bian Dejun; Tian Xi; Zhu Suiyi; Huo Mingxin (Journal of Cleaner Production, 2025)

The long-term environmental evolution of an urban lake in the highly developed Yangtze River Delta - Zhenglan Fu; Longjuan Cheng; Qingfeng Jiang; Jiali Zhang; Xinyue Chen; Shuyi Yang; Xinyuan Gao; Xiang Kuai; Dejun Wan; Dongliang Ning; Bin Xue (Journal of Geographical Sciences, 2025)

Dynamic motion response of a large-scale steel aquaculture cage during towing - Shuai Niu; Zhi Wang; Lianyi Guo; Lianghao Tang; Tianyu Gu; Can Cui; Dejun Feng; Fukun Gui; Xu Yang (Frontiers in Marine Science, 2025)
As global aquaculture ventures further into offshore environments, the safe transport of large-scale aquaculture net cages across varied marine conditions has become a critical technical concern. This study conducts a detailed numerical simulation of the wet towing process for an octagonal aquaculture cage using AQWA software, systematically examining the effects of towline length, towing speed, towing configuration, and environmental factors on the cage’s dynamic response and towline load characteristics. The findings reveal that towline length and towing speed are pivotal in determining the pitch amplitude of the cage and the resulting towline tension. Compared to a towline length of 200 m, using a towline length of 150 m combined with a towing speed of 0.5 m/s reduces pitch amplitude by 51.6% and towline tension by 24.8%. Additionally, an interval towing arrangement significantly enhances cage stability while minimizing towline stress. Under conditions of low wave height and longer wave period, the cage’s motion response remains stable, contributing to enhanced transport safety. This research offers critical theoretical foundations and optimization strategies for the wet towing design considerations of offshore aquaculture cages, providing valuable insights to advance transport safety in challenging marine environments.

Contrasting roles of abundant and rare root-associated fungi in wheat: Community assembly, heritability and agronomic impacts - Xia Kang; Yuyin Zheng; Zhihan Feng; Minjie Yao; Xiangzhen Li; Dejun Han; Qingdong Zeng; Hao Tan; Yumin Yang; Jiabao Li (Applied Soil Ecology, 2025)

Optimisation of peroxide electrocoagulation for the degradation of high concentrations of thiocyanate in heavy metal wastewaters - Lucheng Zhang; Lin Qi; Mingqing Zhang; Kalilou Traore; Zihui Xu; Dejun Yang (Journal of Water Process Engineering, 2025)

New insights into coagulation-enrichment and hydrometallurgical recovery of Sn, Cu, Ni from electroplating wastewater - Htet Oo Kaung; Xin Lan; Minglin Zheng; Dandan Yang; Wu Yang; Yu Chen; Jiancong Liu; Dejun Bian; Hua Kang; Xi Tian; Suiyi Zhu (Journal of Water Process Engineering, 2025)

Comparative efficacy of anaerobic digestion systems in removing antimicrobial resistance genes from swine wastewater - Da Sun; Xiaomin Shi; Yingbo Shen; Ying Liu; Sunlin Luo; Yongpeng Jin; Weishuai Zhai; Lu Liu; Zhaoju Deng; Chengtao Sun; Dejun Liu; Xin Yang; et al. (Journal of Hazardous Materials, 2025)

Laboratory Investigation of the Uplift Resistance of a New Winged H-Pile Anchor Developed for Offshore Marine Aquaculture - Xu Yang; Lianghao Tang; Lili Mei; Tianyuan Zhang; Shuai Niu; Zhefei Sun; Zhenliang Wang; Dejun Feng; Fukun Gui (Journal of Marine Science and Engineering, 2025)
To enhance the stability and safety of marine aquaculture facilities by addressing the limited uplift resistance capacity and susceptibility to deflection of conventional straight-shafted piles, this study introduces an improved H-pile anchor and conducted laboratory experiments. The new anchor incorporates resized H-piles with wing plates added to both sides, optimized for area and placement, as well as an adjusted loading angle. The findings demonstrate a positive correlation between the uplift resistance capacity of the H-pile anchor and its length and width, indicating that while increased pile length significantly enhances resistance, widening has a minimal impact. Additionally, enlarging the wing plate area improves the resistance; however, efficiency (δ) decreases with the increase in the area, suggesting the existence of an optimal size. The optimal wing plate dimensions (L = 80 mm, W = 25 mm) improve uplift resistance by at least 10.6% compared to non-wing pile anchors. Furthermore, positioning the wing plates at the base of the pile anchor rather than the top enhances resistance by approximately 13.8%. Setting the anchor layout angle to 45° reduced the displacement under inclined loads. This research provides essential theoretical support and practical guidance for strengthening the safety and stability of marine aquaculture facilities.

Impact of stocking density of largemouth bass on the self-cleaning performance of a circular aquaculture tank - Xiaoyu Qu; Yi Tao; Dezhen Li; Fuzhi Zu; Yanfei Wu; Fei Wang; Lianhui Wu; Jiajun Hu; Yang Gao; Dejun Feng (Aquaculture, 2025)

Field study on the dynamic characteristics of sewage collection in a circular aquaculture tank - Yanfei Wu; Fukun Gui; Jianxin Yang; Hongfang Qi; Hong Zhang; Yang Wang; Dejun Feng; Qingjing Zhang (Aquaculture International, 2025)

DF-DETR: Dead fish-detection transformer in recirculating aquaculture system - Tingting FU; Dejun Feng; Pingchuan Ma; Weichen Hu; Xinting Yang; Shantan Li; Chao Zhou (Aquaculture International, 2025)

Prevalence and genetic characterization of linezolid resistance gene reservoirs in hospital sewage from Zhejiang Province, China - Weiyi Shen; Yanyan Hu; Dejun Liu; Yang Wang; Stefan Schwarz; Rong Zhang; Jiachang Cai (Science of The Total Environment, 2024)

Sloshing-induced evolution of self-cleaning performance and flow characteristics within a tank installed on an offshore aquaculture vessel - Dezhen Li; Yi Tao; Fuzhi Zu; Yanfei Wu; Fukun Gui; Yang Gao; Fei Wang; Lianhui Wu; Dejun Feng; Xiaoyu Qu (Ocean Engineering, 2024)

Epidemiological and genomic analysis revealed the significant role of flies in dissemination of carbapenem-resistant Enterobacteriaceae (CRE) in China - Hongwei Zhou; Hanyu Wang; Kaichao Chen; Miaomiao Xie; Zelin Yan; Yanyan Zhang; Yuchen Wu; Dejun Liu; Juan Wang; Ning Dong; Chang Cai; Yongning Wu; et al. (Journal of Hazardous Materials, 2024)

Photocatalytic NOx degradation and NO 3 - adsorption by mortar modified with S-g-C3N4/MgAl-CLDH: Influence factors and stability - Lin Lu; Zhengxian Yang; Bo Li; Dejun Ye; Shengyang Luo; Giuseppe Carlo Marano (Journal of Environmental Chemical Engineering, 2024)

The Key Phytochemical Cue Camphor Is a Promising Lure for Traps Monitoring the New Monophagous Camphor Tree Borer Pagiophloeus tsushimanus (Coleoptera: Curculionidae) - Cong Chen; Tian Xu; Shouyin Li; Mingyu Xue; Yadi Deng; Binqi Fan; Chufeng Yang; Dejun Hao (Journal of Chemical Ecology, 2024)

Genomic insights into qnrVC1 gene located on an IncP6 plasmid carried by multidrug resistant Pseudomonas aeruginosa from clinical asinine isolates - Yufei Zhao; Yiping Zhu; Weishuai Zhai; Luo Yang; Cong Peng; Junpeng Mi; Rongzheng Wu; Yuxin Xie; Dejun Liu; Jing Li (Veterinary Microbiology, 2024)

Frequency optimization of the AUV wireless charging system for minimum energy dissipation - Ri Lin; Mingwei Lin; Canjun Yang; Dejun Li; Zhuoyu Zhang (Ocean Engineering, 2024)

A graminan type fructan from Achyranthes bidentata prevents the kidney injury in diabetic mice by regulating gut microbiota - Huayang Si; Yimeng Chen; Dejun Hu; Sainan Yao; Jie Yang; Xiaodong Wen (Carbohydrate Polymers, 2024)

Effect of wing plate structure on uplift resistance capacity of marine aquaculture anchor piles - Fukun Gui; Tianyuan Zhang; Xiaoyu Qu; Xu Yang; Fuxiang Hu; Dejun Feng (Marine Georesources & Geotechnology, 2024)

High-density mapping of durable and broad-spectrum stripe rust resistance gene Yr30 in wheat - Xiaoting Wang; Mingjie Xiang; Huaizhou Li; Xiaoxiao Li; Keqing Mu; Shuo Huang; Yibo Zhang; Xiangrui Cheng; Shuqing Yang; Xunying Yuan; Ravi P. Singh; Sridhar Bhavani; et al. (Theoretical and Applied Genetics, 2024)

Seeding invigoration effect of ice-containing clouds on lower convective clouds during MeiYu season in 2020 - Dejun Li; Chuanfeng Zhao; Jiefan Yang; Cao Liu; Tianyi Wang; Yingying Chen; Ming Li; Zhengteng Yuan; Hai Wang; Jia Fu; Yikun Yang; Yadi Li (Atmospheric Research, 2024)

Study on the effect and regularity of plating parts cleaning wastewater by enhanced aerobic process with high-density bacterial flora - Ying Zhang; Xuejian Sun; Fan Wang; Ting Su; Siwen Yang; Shengshu Ai; Dejun Bian; Hongliang Huo (Journal of Environmental Management, 2024)

Lithologic control of priming effect in subtropical forest - Tiangang Tang; Qi Zhang; Ruitong Fu; Pengpeng Duan; Yuling Zhang; Xinyi Yang; Kelin Wang; Dejun Li (CATENA, 2024)

Factors affecting the enrichment of heterotrophic nitrifying aerobic denitrifying bacteria in municipal wastewater treatment systems and analysis of differences in nitrogen metabolism - Fan Wang; Kailun Yang; Weiqing Jiang; Tong Zhao; Wenai Liu; Xingrong Yao; Dejun Bian (Journal of Water Process Engineering, 2024)

Addition of cellulose and hemicellulose degrading microorganisms intensified nitrous oxide emission during composting - Xinyi Yang; Pengpeng Duan; Qiumei Liu; Kelin Wang; Dejun Li (Bioresource Technology, 2024)

Integration of transcriptomics and metabolomics reveals the effects of sea currents on overwintering of large yellow croaker Larimichthys crocea in cage culture - Huirong Lv; Xiaoyu Qu; Zhangjie Chu; Weiye Li; Xiaolong Yin; Dejun Feng; Jungyeol Park; Junwook Hur; Yang Gao (Aquaculture, 2024)

Tree species diversity increases soil microbial carbon use efficiency in a subtropical forest - Pengpeng Duan; Ruitong Fu; Andrew T. Nottingham; Luiz A. Domeignoz‐Horta; Xinyi Yang; Hu Du; Kelin Wang; Dejun Li (Global Change Biology, 2023)
Plant communities strongly influence soil microbial communities and, in turn, soil carbon (C) cycling. Microbial carbon use efficiency (CUE) is an important parameter for predicting soil C accumulation, yet how plant and soil microbial community traits influence microbial CUE remains poorly understood. Here, we determined how soil microbial CUE is influenced by plant and soil microbial community traits, by studying a natural gradient of plant species diversity in a subtropical forest. Our results showed that microbial CUE increased with increasing tree species diversity, suggesting a correlation between plant community traits and soil C storage. The specific soil properties that explained the greatest variation in microbial CUE were associated with microbial communities (biomass, enzyme activities and the ratio of oligotrophic to copiotrophic taxa); there were weaker correlations with plant‐input properties, soil chemistry and soil organic C quality and its mineral protection. Overall, high microbial CUE was associated with soil properties correlated with increased tree species diversity: higher substrate availability (simple SOM chemical structures and weak mineral organic associations) and high microbial growth rates despite increased community dominance by oligotrophic strategists. Our results point to a mechanism by which increased tree species diversity may increase the forest C sink by affecting carbon use with the soil microbial community.

Mechanisms of mitigating nitrous oxide emission during composting by biochar and calcium carbonate addition - Xinyi Yang; Pengpeng Duan; Yubo Cao; Kelin Wang; Dejun Li (Bioresource Technology, 2023)

Highly effective corneal permeability of reactive oxygen species-responsive nano-formulation encapsulated cyclosporine a for dry eye management - Dejun Yang; Yi Han; Yili Wang; Yingying Pan; Lan Zheng; Zuguo Liu; Cheng Li; Yunlong Wu; Huaqiong Li (Chemical Engineering Journal, 2023)

Mechanisms underlying the responses of microbial carbon and nitrogen use efficiencies to nitrogen addition are mediated by topography in a subtropical forest - Xinyi Yang; Pengpeng Duan; Lettice Hicks; Kelin Wang; Dejun Li (Science of The Total Environment, 2023)

Two-century sediment records of atmospheric mercury variations in North China and their relations with regional and global emissions - Dejun Wan; Handong Yang; Zhangdong Jin; Lei Song; Dongliang Ning; Longjuan Cheng; Qingfeng Jiang (Environmental Science and Pollution Research, 2023)

Evaluating gross primary productivity over 9 ChinaFlux sites based on random forest regression models, remote sensing, and eddy covariance data - Xiaoqing Chang; Yanqiu Xing; Weishu Gong; Cheng Yang; Zhen Guo; Dejun Wang; Jiaqi Wang; Hong Yang; Gang Xue; Shuhang Yang (Science of The Total Environment, 2023)

Study on the Corrosion Behavior of D36 Steel Plate and H62 Copper Alloy Net for Marine Aquaculture Facilities in Simulated Seawater - Fengfeng Gao; Fukun Gui; Dejun Feng; Xiaoyu Qu; Fuxiang Hu; Xu Yang (Journal of Marine Science and Engineering, 2023)
Marine aquaculture facilities have been working in a high salt and humidity marine environment for a long time, which makes them be inevitably affected by seawater corrosion, especially the main structures such as metal mesh and frame. Therefore, studying the corrosion behavior of net and frame steel is of great significance for the selection of materials and corrosion protection of marine aquaculture facilities. The influence of NaCl concentrations and immersion state on self-corrosion behavior and the influence of layer thickness and overlapping area on galvanic corrosion behavior of H62 copper alloy mesh/D36 steel plate was discussed in this study using weight loss and electrochemical measurements. The tensile tests were conducted to observe the influence of different corrosion conditions on maximum force and tensile strength of the net. The corrosion rate of the two materials increased rapidly with the increase of NaCl concentrations; the corrosion rate of both materials showed the decreasing trend with the extension of time, and the corrosion rate of H62 was always lower than D36 steel. When two materials were coupled, the galvanic corrosion rate would decrease with the increase of the layer thickness and overlapping area. The tensile results were consistent with the corrosion results. When these two materials work together, adding layer thickness or increasing the overlapping area is one of the ways to protect the frame steel to a certain extent.

Effect of inlet pipe design on self-cleaning ability of a circular tank in RAS - Yuji Zhang; Xu Yang; Jiajun Hu; Xiaoyu Qu; Dejun Feng; Fukun Gui; Fang Zhu (Frontiers in Marine Science, 2023)
To improve the water reuse efficiency of circular recirculating aquaculture tanks in Recirculating Aquaculture Systems (RAS) this research investigated the effect of inlet pipe deployment distance d (the distance between the stream tube hole and the tank wall) and the inlet pipe deployment angle α (the acute angle between the inlet pipe jetting direction and the nearest tank wall) on the self-cleaning ability of the circular aquaculture tank under dual and single inlet pipe designs. First, waste collection experiments were conducted to figure out the preferable inlet pipe design based on the efficiency of waste collection. Then, flow field measurement experiments were carried out employing the Particle Image Velocimetry (PIV) technique to measure the flow field in the near bottom layer of the tank, and the essential mechanism of the inlet pipe deployment on the waste collection was explored by analyzing the flow field and the corresponding hydrodynamic characteristic indicators, such as the average flow velocity ( v avg ), the uniformity coefficient of water flow (DU50), and the water resistance coefficient (Ct). The results indicate that the variations of waste movement, flow filed and hydrodynamic indicators are consistent in both designs of dual inlet and single inlet, and merely differ in the absolute value. Based on the comprehensive analysis, the optimal performance of self-cleaning can be obtained at α =0°~10°, 20°~30°, 40°~50° for d=1/2 r , 1/4 r , and 1/50 r , respectively. At the same flow rate condition, the jetting velocity of the inlet pipe in the single inlet pipe design is significantly greater than that in the dual inlet pipe design, and the hydrodynamic characteristics of the waste collection are better. Therefore, in circulating water aquaculture production, it is recommended to design the inlet pipe in a similar aquaculture tank to the single inlet pipe with d=1/4 r , α =20°~30°, thus improving the self-cleaning ability of the aquaculture tank. The study results also provide a reference for adjusting the inlet pipe in circular recirculating aquaculture tank.

Correction to: Three novel Fusarium mutualists of ambrosia beetle Euwallacea interjectus in China - Shengchang Lai; Chen Zhao; You Li; Yang Zhou; Lei Zhong; Cailou Qiu; Hua Wang; Yuwen Pan; Lulu Dai; Dejun Hao (Mycological Progress, 2022)

Three novel Fusarium mutualists of ambrosia beetle Euwallacea interjectus in China - Shengchang Lai; Chen Zhao; You Li; Yang Zhou; Lei Zhong; Cailou Qiu; Hua Wang; Yuwen Pan; Lulu Dai; Dejun Hao (Mycological Progress, 2022)

Topography-driven soil properties modulate effects of nitrogen deposition on soil nitrous oxide sources in a subtropical forest - Pengpeng Duan; Xinyi Yang; Xunyang He; Yonglei Jiang; Kongcao Xiao; Kelin Wang; Dejun Li (Biology and Fertility of Soils, 2022)

Underwater Electromagnetic Guidance Based on the Magnetic Dipole Model Applied in AUV Terminal Docking - Ri Lin; Yucheng Zhao; Dejun Li; Mingwei Lin; Canjun Yang (Journal of Marine Science and Engineering, 2022)
To address the poor effect of optical/visual guidance used in AUV terminal docking with strong background light and turbid water quality, an underwater electromagnetic guidance method based on the magnetic dipole model is proposed in this paper. According to the magnetic dipole model, the electromagnetic field of 1 kHz frequency generated by the coil in the range of terminal docking is the near field, where the position can be figured out through the amplitude and phase information of three orthogonal magnetic field intensity vectors. A triaxial-coil magnetometer with three orthogonal coils and a method for extracting the amplitude and phase information of the induced voltage are presented in this paper. According to Faraday’s law, the amplitude and phase information of the induced voltage of a triaxial-coil magnetometer replace the information of magnetic field intensity in relation to positioning. The underwater positioning results show that the average positioning error within 6 m can reach the centimeter level. Five underwater terminal docking tasks were carried out, and four of them were successfully completed, which verified the feasibility of the proposed method.

Application of hydrogen-rich water modulates physio-biochemical functions and early growth of fragrant rice under Cd and Pb stress - Lin Ma; Leilei Kong; Runfei Gui; Xiaojuan Yang; Jianwen Zhang; Qi Gong; Dejun Qin; Maosen Zhuang; Umair Ashraf; Zhaowen Mo (Environmental Science and Pollution Research, 2021)

A multi-proxy record of climate variations over the last millennium from Kulun-nuur Lake sediments, Inner Mongolia, north-central China - Xin Mao; Dejun Wan; Lei Song; Jingsong Yang; Linjing Liu; Gaolei Jiang; Junfeng Li; Xingqi Liu (Journal of Paleolimnology, 2021)

A ~ 230-year dust storm record from China’s Lake Gonghai on the northeast Loess Plateau - Lishuai Xu; Dejun Wan; Yonghong Duan; Yongchong Lin; Guijin Mu; Zhilei Zhen; Yongsheng Yang (Arabian Journal of Geosciences, 2021)

Targeting Human Hippo TEAD Binding Interface with YAP/TAZ-Derived, Flexibility-Reduced Peptides in Gastric Cancer - Dejun Wu; Lijuan Luo; Zhou Yang; Yusheng Chen; Yingjun Quan; Zhijun Min (International Journal of Peptide Research and Therapeutics, 2021)

Record-breaking heat wave in southern China and delayed onset of South China Sea summer monsoon driven by the Pacific subtropical high - Kaiqiang Deng; Song Yang; Dejun Gu; Ailan Lin; Chunhui Li (Climate Dynamics, 2020)
We investigate a record-breaking heat wave in southern China (SC) and explore its association with the South China Sea (SCS) summer monsoon (SCSSM), using station observations and various reanalysis products. This heat wave event started in mid-May 2018 and persisted more than 15 days, when the maximum air temperature anomaly exceeded 6 °C. Meanwhile, the onset of the SCSSM was extremely late in 2018, primarily due to the intrusion of easterly winds over the SCS. We show that the anomalous easterlies over the SCS associated with the delayed SCSSM could block the moisture transport from the tropical oceans to SC, which led to decreased rainfall, increased surface radiation, and elevated probability of heat wave in SC during May 2018. Further analysis reveals that both SC heat waves and SCSSM were significantly affected by the Pacific subtropical high (PSH). The westward extension of the PSH can hinder the establishment of SCSSM via inducing easterly anomalies over the SCS, which reduces SC rainfall and results in a drier surface condition. Moreover, the westward displacement of the PSH may cause anomalously high pressures, descending air motions, and divergent winds over SC, which triggers above-normal air temperatures that are conducive to the occurrences of SC heat waves. This study also underlines the importance of Eurasian planetary wave trains in bridging the upstream climate variability and the changes in PSH during boreal spring, which could be used to improve the intra-seasonal predictions of SC heat wave and SCSSM onset.

Assessing Drought Conditions in Cloudy Regions Using Reconstructed Land Surface Temperature - Shiqi Yang; Dejun Zhang; Liang Sun; Yongqian Wang; Yanghua Gao (Journal of Meteorological Research, 2020)

Prevention and treatment effects of edible berries for three deadly diseases: Cardiovascular disease, cancer and diabetes - Hua Yang; Tiantian Tian; Dianhui Wu; Dejun Guo; Jian Lu (Critical Reviews in Food Science and Nutrition, 2019)

Correction to: Genome-wide mapping of adult plant stripe rust resistance in wheat cultivar Toni - Xinli Zhou; Tian Hu; Xin Li; Ma YU; Yuanyuan Li; Suizhuang Yang; Kebing Huang; Dejun Han; Zhensheng Kang (Theoretical and Applied Genetics, 2019)

Genome-wide mapping of adult plant stripe rust resistance in wheat cultivar Toni - Xinli Zhou; Tian Hu; Xin Li; Ma YU; Yuanyuan Li; Suizhuang Yang; Kebing Huang; Dejun Han; Zhensheng Kang (Theoretical and Applied Genetics, 2019)

Community-wide consistence in plant N acquisition during post-agricultural succession in a karst area, southwest China - Liqiong Yang; Tieguang He; Yuefeng Yu; Zhongyi Li; Dejun Li (New Forests, 2018)

Illumina-based de novo transcriptome sequencing and analysis of Chinese forest musk deer - Zhongxian Xu; Hang Jie; Binlong Chen; Uma Gaur; Nan Wu; Jian Gao; Pinming Li; Guijun Zhao; Dejun Zeng; Mingyao Yang; Diyan Li (Journal of Genetics, 2017)

Evaluation of resistance of current wheat cultivars and breeding lines to stripe rust from three Gorges reservoir area - Yuheng Yang; Fajing Chen; Dejun Han; Renwu Ruan; Boqun Li; Yang Yu; Chaowei Bi (Journal of General Plant Pathology, 2017)

Characterization of a novel micro-pressure swirl reactor for removal of chemical oxygen demand and total nitrogen from domestic wastewater at low temperature - Qingkai Ren; Yang Yu; Suiyi Zhu; Dejun Bian; Mingxin Huo; Dandan Zhou; Hongliang Huo (Biodegradation, 2017)

Molecular cloning and characterization of S-adenosylmethionine decarboxylase gene in rubber tree (Hevea brasiliensis) - Manman Zhao; Hui Liu; Zhi Deng; Jiangshu Chen; Hong Yang; Huiping Li; Zhihui Xia; Dejun Li (Physiology and Molecular Biology of Plants, 2017)

Ammonium-nitrogen-contaminated groundwater remediation by a sequential three-zone permeable reactive barrier (multibarrier) with oxygen-releasing compound (ORC)/clinoptilolite/spongy iron: column studies - Guoxin Huang; Fei Liu; Yingzhao Yang; Xiangke Kong; Shengpin Li; Ying Zhang; Dejun Cao (Environmental Science and Pollution Research, 2015)

Polymorphisms of the IL8 gene correlate with milking traits, SCS and mRNA level in Chinese Holstein - Renjin Chen; Zhangping Yang; Dejun Ji; Yongjiang Mao; Ying Chen; Yunlong Li; Haitao Wu; Xiaolong Wang; Lingling Chang (Molecular Biology Reports, 2011)

Influence of fertilizers on nitrogen mineralization and utilization in the rhizosphere of wheat - Ling Yuan; Dejun J. Bao; Yan Jin; Yuhong H. Yang; Jianguo G. Huang (Plant and Soil, 2011)

Characteristics of the precipitation over the eastern edge of the Tibetan Plateau - Yueqing Li; Dejun Li; Song Yang; Cao Liu; Aihua Zhong; Ying Li (Meteorology and Atmospheric Physics, 2010)

Functional characterization of rice OsDof12 - Dejun Li; Chunhua Yang; Xiaobing Li; Qiang Gan; Xianfeng Zhao; Lihuang Zhu (Planta, 2009)

On-farm estimation of indigenous nitrogen supply for site-specific nitrogen management in the North China plain - Zhenling Cui; Fusuo Zhang; Xinping Chen; Yuxin Miao; Junliang Li; Liwei Shi; Jiufei Xu; Youliang Ye; Chunsheng Liu; Zhiping Yang; Qiang Zhang; Shaomin Huang; et al. (Nutrient Cycling in Agroecosystems, 2008)

Genetic Differentiation of Native Sheep Populations in East and South Asia - Rongqing Geng; Hong Chang; Lanping Wang; K. Tsunoda; Zhangping Yang; Wei Sun; Dejun Ji; Yonghong Li (Biochemical Genetics, 2007)

Biosynthesis and bioactivity of trichosanthin in cultured crown gall tissues of Trichosanthes kirilowii Maximowicz - Hetian Lei; Jianjun Qi; Jingyuan Song; Dejun Yang; Yanzhi Wang; Yinling Zhang; Junshan Yang (Plant Cell Reports, 2006)

Phylogenetic Relationships of Sheep Populations from Coastal Areas in East Asia - Shengxia Lu; Hong Chang; Lei Du; Kenji Tsunoda; Wei Sun; Zhangping Yang; Guobing Chang; Dejun Ji (Biochemical Genetics, 2005)